Evaluating rumen fermentation kinetics and nutritive value of sunflower seed meal supplemented with acetonic extract of pomegranate peel using in vitro gas production technique - Shabnam Nezarati (Acta Scientiarum. Animal Sciences, 2019)
This study was conducted to investigate effects of supplementing different levels (0.0, 0.5 and 1.0% of buffered rumen fluid) of acetonic extract of pomegranate peel on rumen fermentation kinetics of sunflower seed meal (SFM), using in vitro gas production technique. The samples were incubated in syringes containing rumen liquor obtained from three cannulated Iranian Ghezel rams for 2, 4, 6, 8, 12, 24 and 36h. Results indicated that, addition of acetonic extract of pomegranate peel resulted in increase in gas production volume in all of incubation times (p < 0.0001). Amount of gas production, also increased by increasing dose of the extract. Amounts of a (the gas production from the immediately soluble fraction), b (the gas production from the insoluble fraction) and a + b (the potential gas production) for pomegranate peel extract supplemented sunflower seed meal were higher (p < 0.05) than that of control meal. Adding pomegranate peel extract resulted in increase estimated short chain fatty acids (SCFA) production as well as digestible organic matter (DOM), metabolizable energy (ME) and net energy for lactation (NEL) content of SFM. Production of SCFA as well as DOM, ME and NEL content of SFM increased (p < 0.05) by enhancing the level of the extract supplementation. In conclusion, it can be suggest that, supplementing acetonic extract of pomegranate peel may be lead to higher ruminal fermentation and better nutritive value of SFM in ruminants.